2010
DOI: 10.3109/02699051003789260
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of levosimendan on cerebral vasospasm induced by subarachnoid haemorrhage: An experimental study

Abstract: Intravenous levosimendan treatment was found effective by increasing the pathological luminal area and reducing muscular wall thickness measurements. This is the first study to show that intravenous administration of levosimendan is effective in preventing cerebral vasospasm induced by SAH in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Thus, levosimendan should be able to prevent regional no-reflow and hyperperfusion. Moreover, studies have demonstrated an improvement in cerebral perfusion in critically ill infants with low cardiac output syndrome [23] as well as the prevention of vasospasm in an animal model of subarachnoid hemorrhage [24]. However, improved collateral perfusion by levosimendan could not be demonstrated during ischemia in the current investigation, which may indicate that effects on autoregulation during reperfusion play an important role in this model.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, levosimendan should be able to prevent regional no-reflow and hyperperfusion. Moreover, studies have demonstrated an improvement in cerebral perfusion in critically ill infants with low cardiac output syndrome [23] as well as the prevention of vasospasm in an animal model of subarachnoid hemorrhage [24]. However, improved collateral perfusion by levosimendan could not be demonstrated during ischemia in the current investigation, which may indicate that effects on autoregulation during reperfusion play an important role in this model.…”
Section: Discussionmentioning
confidence: 55%
“…Possible targets may include the reduction of cerebral injury after resuscitation, ischemic stroke or cerebral vasospasm [24]. The cardioprotective properties may also be of interest as brain injury may induce heart failure [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although levosimendan delayed reperfusion, we observed an upward shift in the relationship between CBF and MAP, which might counterbalance levosimendan’s direct protective actions. In this context the activation of mK ATP channels and increase of NO release in the vessels by levosimendan was effective and led to vasodilation in the brain as described earlier in an animal model of subarachnoid haemorrhage [42]. In addition, the delayed reperfusion during levosimendan treatment may explain the slower normalisation of the lactate/pyruvate ratio.…”
Section: Discussionmentioning
confidence: 69%
“…Neuronal apoptosis has been reported after CPB (27,28), and Levo has been shown in animal models to have antiapoptotic effects in the myocardium and brain, through its actions on mitochondrial ATP-dependent potassium channels (13,29,30). However, while apopotosis, as indicated by positive TUNEL staining, was present in all study groups, no significant difference was evident in its prevalence between groups.…”
Section: Brain Injury In a Model Of Infant Bypassmentioning
confidence: 80%